Pó da polpa de sapoti obtido em spray dryer: condições de secagem e aplicação em Kefir - Lima, Antonia Carlota de Souza (2024)
Sapodilla is a climacteric fruit species with attractive sensory characteristics, nutritional profile and phytochemical diversity. To increase its popularity, new products can be developed from this fruit. The objective of the research was to evaluate the drying conditions, the influence of different adjuvants, and the application of sapodilla pulp powder obtained in a spray dryer to kefir. Drying conditions were determined with a Rotational Central Compound Design (DCCR), varying the inlet air temperature and adjuvant concentration, analyzing humidity, hygroscopicity and yield. The addition of 20% (m/m) of maltodextrin, gum Arabic and dextrin to the powders was individually evaluated through particle morphology, sorption isotherms and fluidity. The mixture of these adjuvants was studied with a simplex design using humidity, total polyphenols and fluidity of the powders. The stability of the powder containing gum Arabic was evaluated for 120 days. Powdered sapodilla pulp was added to kefir and physical-chemical, microbiological, rheological and sensory analyzes were carried out. The characterization of the pulp showed a polyphenol content of 182.039 mg AGE/100 g. Of the parameters evaluated, only yield presented a significant model, but with a lack of adjustment. The parameters chosen were 20% adjuvant and 160°C temperature. The particles presented a rounded shape with greater roughness in the samples containing gum Arabic. The powder with dextrin resulted in better flow characteristics. The sapodilla pulp powders were classified as cohesive. The isotherms presented a type III format, “J” model, characteristic of sugary products. The mixture of adjuvants significantly influenced (p < 0.1) the characteristics of sapodilla pulp powders, on most of the variables evaluated: humidity (1.17 to 1.56%), Carr index (53.17 to 59 .91%), Hausner ratio (2.2 to 2.5) and polyphenol content (189.95 to 578.56 mg AGE/100 g of pulp solids). The powder containing gum Arabic had lower humidity and hygroscopicity and a higher content of total polyphenols, being stable during the storage period. Kefir formulations presented microbiological standards and chemical composition in accordance with legislation. The addition of the powder increased the content of phenolic compounds in Kefir by up to 272.67%, in addition to the apparent viscosity and shear rate. The formulations showed pseudoplastic behavior. The tasters gave higher marks to Kefir with 20 and 30% powder in all attributes, giving them the terms “creamy”, “full-bodied” and “saboty taste” in CATA. Therefore, powdered sapodilla pulp dried in a spray dryer with gum arabic showed the potential to be used as a stable ingredient, increasing the sensorial acceptance of Kefir by adding flavor and improving its texture according to the notes obtained by the tasters. Therefore, the powder has the potential for versatile food applications that can drive advances in research and the market.